Assessment of alignment of Training, Development and Personal Development Plans of South African Parliament employees: A case study of the Research Unit - Komle, Lindumzi Johnson (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.